The Effect of The Team Game Tournament Learning Model on Student Learning Outcomes - Silvia Diva Sari; Lenti Susanna Saragih (Education and Sociedad Journal, 2026)
This study aims to determine the effect of the Cooperaritve Learning model of the Teams Games Tournament (TGT) type on the learning outcomes of Grade X students at private vocational school. The research method used was a quantitative method with a quasi-experimentas approach. The results of this study indivate that the application of the Team Games Tournament (TGT) learning model has a positive contribution to improving students’ learning outcomes. This is show by the difference in the average learning outcomes between the experimental class and the control class, as well as the hypothesis testing results which indicate a significant effect. It was found that in the control class, the experimental class, the average pretest score was 48.64 and the posttest score was 59.77, while in the experimental class, the average pretest score was 49.79 and the posttest score was 77.92, Meanwhile, based on the analysis results, the significance value (Sih. 2-tailed) was 0.000. This value is lower than 0.05, so H0 is rejected and H1 is accepted. Therefore, it cas be concluded that there is a significant effort of the Teams Games Tournament learning model on students’ learning outcomes.